Anti-Acne Activity of Italian Medicinal Plants Used for Skin Infection - Nelson, Kate; Lyles, James T.; Li, Tracy; Saitta, Alessandro; Addie-Noye, Eugenia; Tyler, Paula; Quave, Cassandra L. (Frontiers in Pharmacology, 2016)
Propionibacterium acnes is implicated in the pathogenesis of acne vulgaris, which impacts >85% of teenagers. Novel therapies are in high demand and an ethnopharmacological approach to discovering new plant sources of anti-acne therapeutics could contribute to filling this void in effective therapies. The aims of our study were two-fold: 1) To determine if species identified in ethnopharmacological field studies as having traditional uses for skin and soft tissue infection (SSTI) exhibit significantly more activity against P. acnes than species with no such reported use; and 2) Chemically characterize active extracts and assess their suitability for future investigation. Extracts of Italian medicinal (for acne and other skin infection) and randomly collected plants and fungi were screened for growth-inhibitory and anti-biofilm activity in P. acnes using broth microdilution methods. Bioactive extracts were chemically characterized by HPLC and examined for cytotoxicity against human keratinocytes (HaCaTs). Following evaluation of 157 extracts from 10 fungi and 58 plants, we identified crude extracts from seven species exhibiting growth inhibitory activity (MICs 64-256 µg mL-1). All active extracts were examined for cytotoxicity against HaCaTs; extracts from one fungal and one plant species were toxic (IC50 256 µg mL-1). HPLC analysis with chemical standards revealed many of these extracts contained chlorogenic acid, p-coumaric acid, ellagic acid, gallic acid and tannic acid. In conclusion, species used in traditional medicine for the skin exhibited significantly greater (p<0.05) growth inhibitory and biofilm eradication activity than random species, supporting the validity of an ethnobotanical approach to identifying new therapeutics. The anti-acne activity of three extracts is reported for the first time: Vitis vinifera leaves, Asphodelus microcarpus leaves and Vicia sativa aerial parts.